Human Resource Management (HR) Strategy in Improving Employee Performance at PT. Riau Islands Port - Satriadi Satriadi; M.Rizky Hidayah Purba; Elly Yantinur; Muhammad Ferry Ramadhan; Synta Synta (Pusat Riset dan Inovasi Nasional, 2025)
: This study aims to analyze HR management strategies at PT. Riau Islands Port in improving employee performance. The research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Based on in-depth interviews with management, it shows that the company implements effective communication strategies, providing incentives, and a collaborative work system. In addition, assignments are tailored to employee characteristics and competencies to ensure performance optimization. The main challenges faced are the differences in work ethic between individuals and the low awareness of some employees in valuing their work, which is overcome through mentorship and competency development. Overall, this strategy contributes to improving employee performance and achieving company goals.